The Effect of Transformational Leadership, Work Culture, and Internal Communication on Employee Performance at PT. Anugerah Manajemen Abadi - Suranti, Dea; Arpah, M.; Rahman, Rahman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Purpose. This study aims to examine the influence of transformational leadership, work culture, and internal communication on employee performance at PT. Anugerah Manajemen Abadi in Batam City. In organizational management, employee performance represents an important indicator of productivity and service effectiveness. Leadership style, organizational values, and communication practices within the workplace are considered key factors that shape employees’ motivation, commitment, and work outcomes. Transformational leadership encourages employees to perform beyond expectations through inspiration and support, while work culture provides shared norms that guide employee behavior. In addition, effective internal communication facilitates coordination and understanding among employees. Understanding the role of these factors is therefore essential for improving employee performance and organizational effectiveness. Materials and methods. This study employed a quantitative explanatory research design using a survey method. The population consisted of all employees working at PT. Anugerah Manajemen Abadi, totaling 40 individuals. Because the population size was relatively small, a saturated sampling technique was applied in which all employees were included as respondents. Data were collected through a structured questionnaire using a five-point Likert scale to measure each research variable. Prior to hypothesis testing, the research instrument was evaluated through validity and reliability tests to ensure the accuracy and consistency of the measurement. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to confirm that the regression model met the required statistical assumptions. Multiple linear regression analysis was then used to examine the influence of the independent variables on employee performance through t-tests, F-tests, and the coefficient of determination (R²). Results. The findings indicate that transformational leadership has a positive and statistically significant effect on employee performance (Sig.=0.000). Internal communication also shows a positive and significant influence on employee performance (Sig.=0.003). In contrast, work culture does not demonstrate a statistically significant effect on employee performance (Sig.=0.924). The simultaneous test shows that transformational leadership, work culture, and internal communication collectively have a significant influence on employee performance (F-test Sig.=0.000). The regression model demonstrates a strong relationship between the variables with a coefficient of determination showing that approximately 80.4% of the variation in employee performance can be explained by the independent variables included in the model. Conclusions. The results of this study highlight the importance of transformational leadership and effective internal communication in improving employee performance within organizations. Although work culture did not show a significant influence in this research, leadership practices and communication systems remain essential factors that shape employees’ productivity and work outcomes. Strengthening leadership strategies that motivate employees and developing transparent communication processes are therefore important steps for enhancing employee performance and supporting organizational success.